1984
DOI: 10.1007/bf01407599
|View full text |Cite
|
Sign up to set email alerts
|

Radioprotection of euoxic bacteria by phenothiazine drugs

Abstract: Survival studies on irradiated euoxic E. coli B/r cells in presence of various concentrations of four radioprotecting phenothiazine drugs have been carried out. Maximum radioprotection was obtained at a optimal concentration for each drug and it decreased on either side of it. The DNA strand break studies at the maximum protective and non-protective concentrations of chlorpromazine and promethazine revealed that the number of ssbs in DNA were less at the protective concentration which were efficiently repaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 18 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…The use of free radical scavengers would allow for biomechanically more stable grafts and the application of higher doses. The most important limitation of free radical scavengers is that they may have radioprotective effect on viral and bacterial DNA; thus, sterility assurance may be affected negatively [4,22]. Basha et al have reported that glycerol had a radioprotective effect on Salmonella whereas cysteamine provided minimal protection [4].…”
Section: Discussionmentioning
confidence: 99%
“…The use of free radical scavengers would allow for biomechanically more stable grafts and the application of higher doses. The most important limitation of free radical scavengers is that they may have radioprotective effect on viral and bacterial DNA; thus, sterility assurance may be affected negatively [4,22]. Basha et al have reported that glycerol had a radioprotective effect on Salmonella whereas cysteamine provided minimal protection [4].…”
Section: Discussionmentioning
confidence: 99%
“…Phenothiazine drugs are known to determined in the liver. Results: The levels of diÚ erent components of the cytochrome interact with cell membranes leading to various P450 system and antioxidant enzymes were enhanced up to 5 Gy changes in membrane characteristics (Seeman 1972, and decreased thereafter. However, a progressive increase was Sheetz and Singer 1974, Paphadijopoulous et al noticed in peroxidative damage and the activities of LDH and 1975).…”
mentioning
confidence: 98%